FOXP2-immunoreactive corticothalamic neurons in neocortical layers 6a and 6b are tightly regulated by neuromodulatory systems - Guanxiao Qi; Danqing Yang; Fernando Messore; Arco Bast; Felipe Yáñez; Marcel Oberlaender; Dirk Feldmeyer (iScience)
Summary: The FOXP2/Foxp2 gene, linked to fine motor control in vertebrates, is a potential candidate gene thought to play a prominent role in human language production. It is expressed specifically in a subset of corticothalamic (CT) pyramidal cells (PCs) in layer 6 (L6) of the neocortex. These L6 FOXP2+ PCs project exclusively to the thalamus, with L6a PCs targeting first-order or both first- and higher-order thalamic nuclei, whereas L6b PCs connect only to higher-order nuclei. Synaptic connections established by both L6a and L6b FOXP2+ PCs have low release probabilities and respond strongly to acetylcholine (ACh), triggering action potential (AP) trains. Notably, L6b FOXP2− PCs are more sensitive to ACh than L6a, and L6b FOXP2+ PCs also react robustly to dopamine. Thus, FOXP2 labels L6a and L6b CT PCs, which are precisely regulated by neuromodulators, highlighting their roles as potent modulators of thalamic activity.